Agromyces arachidis sp. nov. Isolated from a Peanut (Arachis hypogaea) Crop Field - Chandandeep Kaur; Anil Kumar Pinnaka; Nitin Kumar Singh; Monu Bala; Shanmugam Mayilraj (International Journal of Microbiology)
A Gram-positive, yellowish bacterium strain AK-1T was isolated from soil sample collected from peanut (Arachis hypogaea) crop field and studied by using a polyphasic approach. The organism had morphological and chemotaxonomic properties consistent with its classification in the genus Agromyces. Phylogenetic analysis of the 16S rRNA gene sequence showed that strain AK-1T was closely related to Agromyces aurantiacus (98.6%) followed by Agromyces soli (98.3%), Agromyces tropicus (97.6%), Agromyces ulmi (97.3%), Agromyces flavus (97.2%), and Agromyces italicus (97.0%), whereas the sequence similarity values with respect to the other Agromyces species with validly published names were between 95.3 and 96.7 %. However, the DNA-DNA hybridization values obtained between strain AK-1T and other related strains were well below the threshold that is required for the proposal of a novel species. The DNA G+C content of the strain is 71.8 mol%. The above data in combination with the phenotypic distinctiveness of AK-1T clearly indicate that the strain represents a novel species, for which the name Agromyces arachidis sp. nov. is proposed. The type strain is AK-1T (=MTCC 10524T = JCM 19251T).